Organizational Factors Influencing Team Achievements - Maciej SŁOMIAN (Communications of International Proceedings, 2021)
The article attempts to synthesize the newest findings on organizational factors influencing team performance. The analysis was based on the latest literature sources in the field of team management and the effectiveness of team activities. The result is the identification of the factors that should be given the most attention to shape the appropriate attitudes of team members, and thus stimulate the improvement of the results of their work. Three groups of factors influencing team performance have been identified, which include those related to organizational culture and information flow, leadership model, and team members themselves. The added value of the work is the specification of precise features and attitudes that management practitioners should promote in their organizations in order to positively influence the achievements of the teams they manage.
Keywords: Team management; organizational culture; leadership; team achievements.